The spatial production of a border-crossing civil society in Görlitz and Zgorzelec. A German point of view - Teufel Nicolai (Bulletin of Geography. Socio-Economic Series)
After decades of uncertainty and continuous change to the border regime since the split-up of Görlitz into a German part west of the river Neisse, and a Polish part called Zgorzelec after the Second World War, both towns established the self-designated European City Görlitz-Zgorzelec in 1998. Although journalists and politicians maintain that Görlitz and Zgorzelec are a case model for European integration, there are obvious differences between the visions connected to the project ‘European City’ and the everyday life. Following the key research question, whether the ‘European City Görlitz-Zgorzelec’, in its attempts to develop a border-crossing civil society, is also constructed from below by citizens on both sides of the border, my contribution to the field of border studies uses a qualitative micro-level approach to these processes in the fields of culture, leisure and education. For that aim, an ethnographically inspired socio-geographical research design has been linked to Henri Lefebvre’s theoretical framework of the double triad of spatial production developed in The Production of Space (1991). From the perspective of actors in civil society in both towns, who are active in constructing, shifting and deconstructing borders, the article aims to illuminate both territorial and social bordering processes. Borderwork is embedded in and connected to transformation and peripheralisation processes, as well as to the discourses on and the funding instruments of European Integration in the context of the complex history of the Polish-German border.